Democratization or Extra-Constitutionalism: Ideas for Limiting the Term of Office for Chairmen of Political Parties in Indonesia - Mukhlis, Muhammad Mutawalli; Tajuddin, Muhammad Saleh; Ilham, Ilham; Koharudin, Koharudin; Rahman, Abdul (Jambura Law Review, 2024)
One aspect of the internal democratization of political parties that is not working is the lack of regeneration of political party leaders. This phenomenon presents oligarchic party practices and gives rise to a very elitist and feudalistic culture since political parties are controlled by the general chairman. This research is qualitative research with normative juridical methods using legal, conceptual, philosophical, and doctrinal approaches. This research is library research that examines and explores regulatory documents, books, journals, and other scientific works that are relevant to the topic of discussion. This article aims to provide new thinking in building internal institutions of democratic political parties. The results of data collection were analyzed in depth and then presented descriptively analytically. The conclusion of the article shows that by limiting the term of office of the general chairman of a political party, party internalization becomes more open. This idea advances party organizations that prioritize healthy competition. The terms of office need to be regulated in the political party law and do not need to be regulated in the political party's articles of association and bylaws for the sake of uniformity and legal certainty. The term of office of a political party leader is limited to 1 (one) period, namely five years, and a maximum of 2 (two) periods, namely ten years, if re-elected as general chairman at the political party conference forum and chairman election.